2006
DOI: 10.1103/physrevlett.96.246101
|View full text |Cite
|
Sign up to set email alerts
|

In SituSurface X-Ray Diffraction Studies of Homoepitaxial Electrochemical Growth on Au(100)

Abstract: Direct in situ x-ray surface scattering studies of growth at a solid-liquid interface are demonstrated using the homoepitaxial electrodeposition on Au(100) as an example. With decreasing potential transitions from step-flow to layer-by-layer growth, manifested by layering oscillations in the x-ray intensity, then to multilayer growth, and finally back to layer-by-layer growth were observed. This complex growth behavior can be explained by the effect of anion coadsorbates and the potential-dependent Au surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 18 publications
11
62
0
Order By: Relevance
“…These studies revealed a layer-by-layer dissolution mechanism for the electrochemical dissolution of Au(111) up to the onset of passivation 12 and a complex, potential-dependent growth behavior, featuring step-flow, layer-by-layer, 3D, and re-entrant layer-by-layer growth, for the homoepitaxial electrodeposition of Au on Au(001). 10,11 Here we demonstrate for the case of electrochemical dissolution of Au(001) that, even at rates approaching those employed in technological deposition and dissolution processes, atomicscale data can be obtained by in situ surface X-ray diffraction. Key to this improvement was the implementation of a fast 1D X-ray detector (Dectris Mythen 1K).…”
mentioning
confidence: 98%
“…These studies revealed a layer-by-layer dissolution mechanism for the electrochemical dissolution of Au(111) up to the onset of passivation 12 and a complex, potential-dependent growth behavior, featuring step-flow, layer-by-layer, 3D, and re-entrant layer-by-layer growth, for the homoepitaxial electrodeposition of Au on Au(001). 10,11 Here we demonstrate for the case of electrochemical dissolution of Au(001) that, even at rates approaching those employed in technological deposition and dissolution processes, atomicscale data can be obtained by in situ surface X-ray diffraction. Key to this improvement was the implementation of a fast 1D X-ray detector (Dectris Mythen 1K).…”
mentioning
confidence: 98%
“…For example, the 3D to 2D growth transition in the homoepitaxial growth on Pt(1 1 1) in ultrahigh vacuum (UHV) can be attributed to the formation of a high-temperature surface reconstruction [3]. Similar phenomena can occur in electrochemical homoepitaxial growth as we have recently demonstrated for Au(1 0 0) electrodeposition, where a similar ''reentrant'' 2D growth was observed in the potential regime of the Au reconstruction [4]. Here we will show that also on Au(1 1 1) the presence of the surface reconstruction strongly influences the growth behavior, resulting in the formation of well-defined nanoscale grooves on the surface.…”
Section: Introductionmentioning
confidence: 61%
“…7,8,[54][55][56][57][58][59] These investigations provide unparalleled insight into single crystal homoepitaxial growth at the solid-liquid interface, which can deviate significantly from features observed in systems operated under ultra-high vacuum. 60 The homoepitaxial system was used to validate the results in this paper against previously published surface nucleation and growth calculations.…”
Section: Resultsmentioning
confidence: 99%